“Harmonizing”: Integrative and complementary practices in university extension (Research, Society and Development, 2021)
Introduction: With the creation of the National Policy on Integrative and Complementary Practices (PNPIC), in May 2006, a new context for the insertion of these resources in the Unified Health System (SUS) was opened, also requiring approximation and studies during the professional training, so that students can reflect, experience and analyze these practices even during their undergraduate course, with university extension being a possible field of opportunities for the development of therapeutic plurality, favoring closer ties between university and community. Objectives: To assess the perceptions, difficulties and repercussions that the experiences with PICS provided in the academic and personal life of students who were extensionists in projects involving integrative and complementary practices. Methodology: Qualitative, exploratory and descriptive research, conducted with 7 students from the Nursing, Pharmacy and Nutrition courses at the Federal University of Campina Grande. The collection of data took place through semi-structured interviews, and they were analyzed using the content analysis technique. Results and Discussions: The integrative practices act in the care of oneself and of the other, in an ethical perspective of care, adding theoretical and practical knowledge and transforming the personal reality of the subjects. Nevertheless, there are many challenges ahead, such as little dissemination, disbelief in the beneficial effects and the hegemony of the biomedical model in the construction of health courses, which makes it difficult to expand these therapies. Conclusion: It is essential to expand the academic spaces for discussion and development of integrative and complementary practices, enhancing and integrating these resources in the training of health students, in the three inseparable spheres of the institution: teaching, extension and research.